Health policy response to mobility during the pandemic: Evaluating the effectiveness using location‐based services big data. (28th May 2022) - Yuan, Bocong; Zhao, Hairong; Li, Jiannan
Abstract: As an emergent health policy response, the population mobility restriction policy was implemented to cope with the unprecedented pandemic that outbroke in early 2020, but its effectiveness showed vast disparities even within a single country. Using multisource data from Baidu mobility big data and the statistics of novel coronavirus disease in China, mobility restrictions (including restrictions on inflow‐mobility, outflow‐mobility, and intra‐city mobility) were examined. It was found that the mobility restriction had contained the development of pandemic, but such effect would gradually recede over time. Moreover, there existed region‐specific policy effectiveness. Specifically, outflow‐mobility restrictions were ineffective in reducing death cases in population influx areas, and restrictions on inflow‐mobility (or intra‐city mobility) were ineffective in reducing confirmed cases (or death cases) in population outflow areas. It was concluded that the mobility restriction policy can be effective in epidemic prevention and control in spatial‐temporal pattern. However, there was a remarkable disparity in policy effectiveness between different regions with different population mobility patterns. Highlights: The effectiveness of health policy response to population mobility is examined. The location based‐service big data are applied to measure the mobility restriction policy response. Different types of mobility restriction policy are investigated. The effectiveness of policy response is investigated in areas with different trend of population mobility.